Splenic dendritic cell subsets prime and boost CD8 T cells and are involved in the generation of effector CD8 T cells. - Behboudi, S; Moore, A; Hill, A (2004)
The ability of the dendritic cell (DC) subsets, CD8alpha+ and CD8alpha- DCs, to initiate a CD8 T cell response or to activate memory CD8 T cells and generate effector CD8 T cells has been controversial. In this study, we analyse the capacity of splenic DC subsets to induce CD8 T cell responses to a CD8 T cell epitope (pb9) of a malaria antigen. The administration of peptide-pulsed CD8alpha- or CD8alpha+ DCs primes and boosts a primed CD8 T cell response against the malaria epitope. In vitro, depletion of CD11c(+) DCs from mouse splenocytes, immunised with recombinant vaccinia virus Ankara (MVA) expressing pb9 epitope, significantly reduced the generation of pb9-specific IFNgamma producing effector CD8 T cells, indicating that splenic DCs are involved in the development of pb9-specific IFNgamma producing effector cells. Taken together, this result shows that both DC subsets have the ability to prime and boost CD8 T cell responses and are involved in the activation of memory CD8 T cells.